A two stage battery charger for EV charging applications - V. Kalyanasundaram; George S Fernandez; K. Vijayakumar; S. Vidyasagar (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Electric power generation and consumption are indicating an unprecedented change in recent decades. Electrical power industry and transportation sector lie at the core of this development and hence this change. This change is one of the major causes of polluting environmental and global warming. So, to decrease the dependency on conventional fuels and greenhouse gas emissions, countries around the globe are actively finding alternative energy resources. It will help to develop clean and green energies to build a sustainable society. Simultaneously, energy utilization in the field of transportation is witnessing a change from fossil fuel to electricity-based fuel. Electrified transportation system is a solution to endorse sustainable energy development and addressing environmental pollution, global warming issues. In this paper, an EV battery charger is designed with a two-stage charging model to achieve good efficiency. The design is simulated by using MATLAB simulation and compared with the existing model. The simulation results show that the proposed model is superior to the traditional model.